Gambaran Pengetahuan Masyarakat Terhadap Penggunaan Analgesik OTC (Over The Counter) Di Kecamatan Wawonii Timur Kabupaten Konawe Kepulauan Provinsi Sulawesi Tenggara - Yuliana, Dewi (Makassar Pharmaceutical Science Journal (MPSJ), 2024)
Analgesics are substances or drugs that can be used to reduce pain without losing consciousness. This drug is the most widely used type of drug in self-medication in society. This study aims to describe the knowledge of the people of East Wawonii District, Konawe Islands Regency, Southeast Sulawesi Province. This research was conducted by giving questionnaires to respondents, namely the people in East Wawonii District, Konawe Islands Regency, which then collected data and analyzed it descriptively. The sampling method used was purposive sampling and the number of samples was calculated using the slovin formula. The results showed that people in East Wawonii District, Konawe Islands Regency, Southeast Sulawesi Province already had knowledge that was included in the fairly good category regarding the use of OTC (Over The Counter) analgesics with a percentage of 73%.